Moderating Influence of Stakeholder Knowledge on the Relationship between Social Reporting and Sustainability Accounting in the Tea Sector in Mount Kenya Region - Sylvester Onyango; Stephen Wanyoike Muchina; Stephen Irura Ng'ang'a (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2019)
In accounting, financial reporting dominantly focus on profits. There is growing pressure on social sensitivity of accounting. Sustainable Development Goals advocate for concern to the environment. Some researchers have endeavored to demonstrate how accountancy need to respond to the social concerns beyond traditional goal of profit maximization that singles out shareholders from the many stakeholders. However, these studies have been deficient in addressing the moderating influence of stakeholder knowledge on the relationship between social reporting and sustainability accounting which this study explores. The study adopted Mixed Methods Research of survey design. The target population comprised of the factory unit managers and accountants as the key informants, drawn from tea factories of Mount Kenya region. The sample was obtained by simple random and stratified sampling techniques. Questionnaire was the main data collection instrument. Data analysis entailed simple binary and hierarchical multiple logistic regression analysis using SPSS. Study results was presented in frequencies, percentages and skewness for descriptive and binomial regression output for inferential statistic. The study found out that tea factories practice social activities that they incur costs which were treated as overhead costs and benefits were derived by tea factories. There was a statistically significant influence of social reporting on sustainability accounting; which was insignificantly moderated by stakeholder knowledge. The study findings were of significant to organizations’ strategies to respond to social externalities which in accounting terms affect the organizations profits in the long run. The study recommends tea factories adopt an integration of social reporting and financial reporting without much focus on stakeholder knowledge.